The Second Iraq War’s Background: How Does War Stimulate It? - Çınar, Selin (Pakistan Review of Social Sciences (PRSS), 2023)
As a result of the Iraq War in the Middle East dating back to the very early years, conflicts have been ongoing in the 1980s. As a result, the main causes of the conflicts in Iraq can be traced back to the First Gulf War in August 1990. The war began in Iraq and Kuwait, but it spread around the world under the leadership of the United States, one of the most powerful actors, and ended with the 2003 conflict with Iraq. When we specifically examined the Iraq War in 2003, we focused on U.S. and United Kingdom effects. This study is mostly an attempt to, for all intents and purposes, understand how the Iraq War stimulated the conflicts in non-direct and direct ways, with the being the major way.